(untitled) (Huellas, 2023)
The vast academic production within the framework of gender studies in social sciences in general offers multiple concepts and analysis tools that can operate as triggers for inquiry. This article presents a brief historical description of the main contributions developed in anthropology and geography of gender and a theoretical and methodological approach for the analysis of gender problems arising in a particular rural context that is positioned at the intersection between human geography and social anthropology. This is the result of a research proc-ess conducted with families living in the Forest Centre Area in the Lower Delta of the Paraná River.